Isolation and in vitro characterization of novel S. epidermidis phages for therapeutic applications - Štrancar, Vida; Marušić, Monika; Tušar, Jasmina; Praček, Neža; Kolenc, Marko; Šuster, Katja; Horvat, Simon; Janež, Nika; Peterka, Matjaž (Frontiers in Cellular and Infection Microbiology, 2023)
S. epidermidis is an important opportunistic pathogen causing chronic prosthetic joint infections associated with biofilm growth. Increased tolerance to antibiotic therapy often requires prolonged treatment or revision surgery. Phage therapy is currently used as compassionate use therapy and continues to be evaluated for its viability as adjunctive therapy to antibiotic treatment or as an alternative treatment for infections caused by S. epidermidis to prevent relapses. In the present study, we report the isolation and in vitro characterization of three novel lytic S. epidermidis phages. Their genome content analysis indicated the absence of antibiotic resistance genes and virulence factors. Detailed investigation of the phage preparation indicated the absence of any prophage-related contamination and demonstrated the importance of selecting appropriate hosts for phage development from the outset. The isolated phages infect a high proportion of clinically relevant S. epidermidis strains and several other coagulase-negative species growing both in planktonic culture and as a biofilm. Clinical strains differing in their biofilm phenotype and antibiotic resistance profile were selected to further identify possible mechanisms behind increased tolerance to isolated phages.